Pengembangan Bahan Ajar Fikih Berbasis Padlet dalam Meningkatkan Motivasi Belajar Siswa di MTs Al-Azhar Pamekasan - Mabnunah, Mabnunah; Nafilah, Anis Khofifatun; Zainab, Nurul (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
Learning materials are the key to the success of the learning process. The development of learning materials is carried out by taking into account the characteristics and conditions of the learners, as well as their relevance to the development of the times. The use of technology has also been integrated to create up-to-date learning. However, the gap in access to technology between urban and rural areas still needs attention. Therefore, the purpose of this study is to test the development of Padlet-based Fiqh learning materials to improve student motivation in MTs Al-Azhar Pamekasan. This study uses the R&D method through the development of Padlet-based Fiqh learning materials with the ASSURE model. It also uses the linear regression formula to ensure the influence of learning material development on the motivation of Grade 8 students at MTs Al-Azhar.The findings of the study prove that the development of Padlet-based Fiqh learning materials is very effective in attracting interest and livening up the learning atmosphere in the classroom. Through regression analysis testing, the development of this fiqh learning material is also able to increase student motivation from various aspects.